2015
DOI: 10.1016/j.soard.2014.10.027
|View full text |Cite
|
Sign up to set email alerts
|

Health-related quality of life after bariatric surgery: a systematic review of prospective long-term studies

Abstract: Impaired health-related quality of life (HRQoL) is common in bariatric surgery candidates and is often one of the motivating factors for seeking bariatric surgery. Although many studies have reported changes in HRQoL after bariatric surgery, few are long-term prospective studies and no systematic review has been conducted. A systematic database search identified studies reporting HRQoL preoperatively and ≥ 5 years after bariatric surgery. Change in HRQoL over time was the outcome variable, divided into primary… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

9
105
0
4

Year Published

2016
2016
2022
2022

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 133 publications
(118 citation statements)
references
References 40 publications
9
105
0
4
Order By: Relevance
“…9 Studies have also shown a 50% reduction in mortality after bariatric surgery and an improvement in the quality of life of patients that accompanies their weight loss and improvement in overall health. 10,11 The objective of this study was to publish short-term outcomes after bariatric surgery in Canada's largest regional bariatric surgery program, and to compare short-term outcomes between sites. We hypothesize that outcomes of the Ontario Bariatric Network would be similar to other major international centres, with little variation across centres within the program.…”
mentioning
confidence: 99%
“…9 Studies have also shown a 50% reduction in mortality after bariatric surgery and an improvement in the quality of life of patients that accompanies their weight loss and improvement in overall health. 10,11 The objective of this study was to publish short-term outcomes after bariatric surgery in Canada's largest regional bariatric surgery program, and to compare short-term outcomes between sites. We hypothesize that outcomes of the Ontario Bariatric Network would be similar to other major international centres, with little variation across centres within the program.…”
mentioning
confidence: 99%
“…Compared to gastric bypass, BPDDS is associated with higher loss and remission rates for metabolic diseases [10]. A recent systematic review identified seven prospective cohort studies reporting HRQL both preoperatively and > five years after bariatric surgery [11]. Of these studies, only one reported 10-year HRQL data, but no studies included BPDDS [12].…”
Section: Introductionmentioning
confidence: 99%
“…No relationship emerged between weight loss and psychological QoL, a finding that was confirmed by other cohort studies with longer follow-up periods Kolotkin et al 2012;Herpertz et al 2015). Andersen et al (2015) conducted a systematic review on the QoL of bariatric surgery patients, and included studies with a follow-up of at least five years only. Overall, seven studies were considered Mathus-Vliegen 2007;Helmiö et al 2011;Schouten et al 2011;Kolotkin et al 2012;Zijlstra et al 2013;Aasprang et al 2013), comprising a total of 1,113 patients, observation periods from 5 to 10 years, and follow-up rates from 61% to 92%.…”
Section: Quality Of Life (Qol)mentioning
confidence: 80%